1984
DOI: 10.1093/clinchem/30.8.1286
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of protein-calorie malnutrition.

Abstract: We critically review the various methods for assessing protein--calorie malnutrition. These tests are lacking in sensitivity and specificity, and currently no single one can be used as a reliable indicator of malnutrition. However, a combination of several of them can be used as prognostic indicators and are of help in selecting patients who may benefit from nutritional support. Body-composition analyses and functional tests hold the promise of greater applicability in the future. Newer and more nearly accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Gómez-Ambrosi et al observed a decrease in RBP-4 levels only after gastric bypass surgery with concomitant pronounced reductions in total-fat mass, postulating that RBP-4 might be considered as a dynamic marker of negative energy balance (41). Decreasing RBP-4 levels being associated with malnutrition has also been shown in previous investigations (42). However, in our study, data from intermediate routine follow-ups showed that all but four patients were weight stable (<5% variation) within 3 months before follow-up.…”
Section: Table 3 Cross-correlation Matrix For Changes In Parameters Omentioning
confidence: 54%
See 1 more Smart Citation
“…Gómez-Ambrosi et al observed a decrease in RBP-4 levels only after gastric bypass surgery with concomitant pronounced reductions in total-fat mass, postulating that RBP-4 might be considered as a dynamic marker of negative energy balance (41). Decreasing RBP-4 levels being associated with malnutrition has also been shown in previous investigations (42). However, in our study, data from intermediate routine follow-ups showed that all but four patients were weight stable (<5% variation) within 3 months before follow-up.…”
Section: Table 3 Cross-correlation Matrix For Changes In Parameters Omentioning
confidence: 54%
“…However, in our study, data from intermediate routine follow-ups showed that all but four patients were weight stable (<5% variation) within 3 months before follow-up. In addition, measurements of transferrin, which can also serve as a marker for malnutrition (42), were performed. Despite a significant decrease, baseline and follow-up values of all subjects were within the normal range and analysis revealed no association between RBP-4 and transferrin levels with regard to baseline, follow-up, or longitudinal measurements.…”
Section: Table 3 Cross-correlation Matrix For Changes In Parameters Omentioning
confidence: 99%
“…The different groups of nutritional status are those defined by Waterlow [ 161. The following levels of plasma proteins were considered abnormal as proposed in the literature [17]: Alb < 3.5 g/dl, RBP < 3 mg/dl, Tr < 200 mg/dl.…”
Section: Patientsmentioning
confidence: 99%
“…To detect depletion of protein supplied as well as metabolic alterations related to the malnutrition of tissues, invasive techniques such as measurement of biochemical indicators are required. The most widely used chemical indicators are visceral circulating proteins secreted by the liver (Haider and Haider 1984). These proteins, especially those with a quick turnover and a medium half-life, such as C reactive protein or prealbumin (Ingenbleek et al 1972), are useful for detecting subclinical and early stages of malnutrition.…”
Section: Biochemical Methodsmentioning
confidence: 99%